(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article focuses on the implementation of ethnographic research in world and Uzbek linguistics, and its study in folklore, dialect, and ethnocultural aspects is highlighted.